ANTIOXYDANT AND INSECTICIDAL ACTIVITY OF ALGERIAN MYRTUS COMMUNIS L. EXTRACTS - IAZZOURENE, GHANIA; MOUHOUCHE, FAZIA; HAZZIT, MOHAMED (My University, 2014)
This study was designed to examine the antioxidant and insecticidal activity of the essential oils and methanolic extracts of M.communis grown in three different areas of Algeria. Myrtle leaf was the valuable organ for the essential oil production representing a yield between 0.33 and 0.41 % (w/w). Leaves methanol extract was analyzed in terms of the dosage in total phenolic and flavonoids contents. Gallic acid equivalent representing total phenolic constituents of methanolic extracts were 78.79, 75 and 83.03 mg GAE/g; and Quercetin equivalent representing total flavonoids were 21.61, 16.81 and 17.42 mg QE/g of myrtle from Tizi Ouzou, Hamam Melouan and Tablat respectively. Antioxidant activity of the essential oil and the methanolic extract from different myrtles were evaluated by using DPPH radical scavenging, methanolic extracts of different myrtle showed better antioxidant activity than essential oils. The samples were tested for their insecticidal activity against adults of S.oryzae(L.) and T. confusum (Duv), using direct contact application and fumigation methods
Keywords: Myrtus communis; Essential Oil; Methanol Extract; Antioxidant and Insecticidal Activity